Behaviour of cold-formed steel composite floor section in light steel framing for vertical orientation [electronic resource] - Muhammad Zakwan Mohamed Yussof, 1989-; Tan, Cher Siang, supervisor (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2012